If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 9 = 4(-1x) Reorder the terms: 9 + 6x = 4(-1x) Remove parenthesis around (-1x) 9 + 6x = 4 * -1x Multiply 4 * -1 9 + 6x = -4x Solving 9 + 6x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 9 + 6x + 4x = -4x + 4x Combine like terms: 6x + 4x = 10x 9 + 10x = -4x + 4x Combine like terms: -4x + 4x = 0 9 + 10x = 0 Add '-9' to each side of the equation. 9 + -9 + 10x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 10x = 0 + -9 10x = 0 + -9 Combine like terms: 0 + -9 = -9 10x = -9 Divide each side by '10'. x = -0.9 Simplifying x = -0.9
| x^2(2x+3)+2x(3x^2+5x)= | | 24-2t-t^2=0 | | x^3+3x^2=4x-12 | | 15-(-7x)+5x-(-9)= | | 8*n=56 | | X^3-7x-18x=0 | | 7-y-6=-1 | | (n-6)+12=24 | | 6x-48=46 | | 8e+(5-e)=30 | | 7a+8b=11-5c | | -134-2x=-10x+58 | | 6*-48=46 | | 20=140 | | 3x^2=3x+60 | | 2(3d+6)=24 | | 4(2n-5)=-20+8n | | 2p^2-10p+12=0 | | 8e+5-e=30 | | 15x+4=12x+22 | | 4(2a+2b)= | | 8x-(-3)=11 | | 2x=ax+B | | -12x-77=27-8x | | 6x-6x+2= | | 5n-6=12 | | 7.1x=-14.2 | | 2x+2+x=4 | | 5t-18=2 | | -8x+6-6=5-6 | | 2x^2+25x-6.5=0 | | x^2+x^2+x^3= |